Role of 5-HT1A-mediated upregulation of brain indoleamine 2,3 dioxygenase 1 in the reduced antidepressant and antihyperalgesic effects of fluoxetine during maintenance treatment - Dai, Jiajia; Kim, Hyangin; You, Zerong; McCabe, Michael F.; Zhang, Shuzhuo; Wang, Shiyu; Lim, Grewo; Chen, Lucy; Mao, Jianren (Frontiers in Pharmacology, 2022)
The reduced antidepressant and antihyperalgesic effects of selective serotonin reuptake inhibitors (SSRIs) such as fluoxetine during maintenance treatment has been reported, but little is known about the molecular mechanism of this phenomenon. In three comorbid pain and depression animal models (genetic predisposition, chronic social stress, arthritis), we showed that the fluoxetine’s antidepressant and antihyperalgesic effects were reduced during the maintenance treatment. Fluoxetine exposure induced upregulation of the 5-hydroxytryptamine 1A (5-HT1A) auto-receptor and indoleamine 2,3 dioxygenase 1 (IDO1, a rate-limiting enzyme of tryptophan metabolism) in the brainstem dorsal raphe nucleus (DRN), which shifted the tryptophan metabolism away from the 5-HT biosynthesis. Mechanistically, IDO1 upregulation was downstream to fluoxetine-induced 5-HT1A receptor expression because 1) antagonism of the 5-HT1A receptor with WAY100635 or 5-HT1A receptor knockout blocked the IDO1 upregulation, and 2) inhibition of IDO1 activity did not block the 5-HT1A receptor upregulation following fluoxetine exposure. Importantly, inhibition of either the 5-HT1A receptor or IDO1 activity sustained the fluoxetine’s antidepressant and antihyperalgesic effects, indicating that 5-HT1A-mediated IDO1 upregulation in the brainstem DRN contributed to the reduced antidepressant and antihyperalgesic effects of fluoxetine. These results suggest a new strategy to improving the therapeutic efficacy of SSRI during maintenance treatment.